2021
DOI: 10.1093/ofid/ofab466.003
|View full text |Cite
|
Sign up to set email alerts
|

3. Stopping Hospital Infections with Environmental Services (SHINE): A Cluster-Randomized Trial of Intensive Monitoring Methods for Terminal Room Cleaning on Rates of Multidrug-Resistant Organisms (MDROs) in the Intensive Care Unit (ICU)

Abstract: Background MDROs frequently contaminate hospital environments. We performed a multicenter cluster-randomized, crossover trial of two methods for intensive monitoring of terminal cleaning effectiveness at reducing infection and colonization with MDROs within ICUs. Methods Six medical and surgical ICUs at three medical centers received both intensive monitoring interventions sequentially, in a randomized order. The intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other studies have also shown a reduction in HAIs with enhanced cleaning and associated disinfection. [31][32][33][34][35][36][37][38][39] The limitations of our study are, in some ways, its strength. We did not attempt to control room selection or rigidly monitor participant (nursing or housekeeping) activities aside from ongoing education and regular performance feedback.…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have also shown a reduction in HAIs with enhanced cleaning and associated disinfection. [31][32][33][34][35][36][37][38][39] The limitations of our study are, in some ways, its strength. We did not attempt to control room selection or rigidly monitor participant (nursing or housekeeping) activities aside from ongoing education and regular performance feedback.…”
Section: Discussionmentioning
confidence: 90%